Immunohistochemical study of p53, Ki-67, epidermal growth factor receptor, and sex-determining region Y-box 2 in squamous cell carcinoma of tongue - Pallavi D Bhayekar; Vandana L Gaopande; Avinash R Joshi; Amruta B Jadhav (Wolters Kluwer Medknow Publications, 2016)
Objective: Tongue cancer (TC) is one of the most common oral cancers. Prognostic evaluation of this tumor includes histologic grade and TNM stage. In this study, we evaluated the expression of p53, Ki-67, epidermal growth factor receptor (EGFR), and sex-determining region Y-box 2 (SOX2) and correlated it with the clinicopathologic variables to assess their potential for use as prognostic markers. We compared the p53 positive and negative group. Design: A retrospective and prospective study with 45 cases of biopsy proven TC which were studied for the expression of p53, Ki-67, EGFR, and SOX2. The results were correlated with known clinicopathologic variables using Chi-square test. The p53 positive and negative groups were compared. Materials and Methods: Archieved blocks of biopsy proven TC were retrieved. Using 4 micron sections of the blockes immunostaining for p53, Ki67, EGFR and SOX2 was done. Results: P53 expression was 68.9%, Ki-67 was 88.9%, EGFR was 48.9%, and SOX2 was 35.6%. Expression of p53 and Ki-67 did not show any correlation with any of the clinicopathologic variables. There was a statistically significant association between EGFR expression and lymph node (LN) positivity (P = 0.001). Stage of tumor and SOX2 positivity showed a significant correlation (P = 0.03). The comparison of p53 positive and negative groups did not reveal a significant difference. Conclusion: p53-negative TC is not significantly different from the p53-positive TC at presentation. The absence of mutant p53 in more than 30% TC points toward the possible etiological role of human papillomavirus in TC. Larger studies are needed to evaluate the possible use of EGFR for prediction of LN metastasis and SOX2 as a prognostic marker.